Atributos de qualidade em sementes de trigo recobertas com zinco durante e após armazenamento - Tunes, Lilian Vanussa Madruga de (2011)
Seed coating treatments are among the most interesting and potentially beneficial for enhancing the performance of the same. This fact, which helps the producer to improve the performance and development of seedlings, with the possibility the use of micronutrients such as zinc, in the seeds. Our objectives were to evaluate the effect of wheat seed coating with zinc through the physiological, sanitary and enzyme quality, during storage and analyze the effect of this nutrient, on nutrition early growth of seedlings and on the components of income after storage. Were tested for levels 0, 1, 2, 3 and 4 mL ZnSO4.kg-1 seed, high and low quality, for the seed quality physiological, sanitary and enzyme, six months of storage. After the storage period, we assessed the dry mass, zinc content and accumulation in shoots and roots of wheat plants. We also evaluate the efficiency of absorption, transport and use of zinc in addition to verification of the yield components. We conclude that the ZnSO4 assists in maximum expression of seed quality. There are variations in the pattern of expression of the enzymes EST, GOT and GTDH. The micronutrient zinc, associated with fungicide and polymer, showed a lower incidence of fungi during the storage period. The application of ZnSO4 in seeds causes a higher dry matter and zinc content in the roots. Zinc applied to wheat seeds accumulate mainly in roots. The application of ZnSO4 in seeds resulting in higher absorption efficiency and lower transport efficiency and use of Zn, as we increase the doses of the nutrient. Considering the results of the yield components, number of grains per spikelet and grain weight per plant, it can be said that the wheat seed coating with zinc provides a productivity increase of more than 30%.